The need to improve pig feeding options - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Izdebski, W. (ТДАТУ, 2020)
The basis of the new system is the digestion unit, which calculates the quantitative composition of the individual nutrients that are absorbed, rather than digested raw nutrients. On how exactly these indicators will be calculated, the further operability of the entire system will depend. In this regard, there is a need to study the digestive processes on issues related to the development of the final digestion products.
Keywords: the norms of feeding; harvesting technology; digestion; feed